2017
DOI: 10.1002/2017je005343
|View full text |Cite
|
Sign up to set email alerts
|

Dioctahedral Phyllosilicates Versus Zeolites and Carbonates Versus Zeolites Competitions as Constraints to Understanding Early Mars Alteration Conditions

Abstract: Widespread occurrence of Fe,Mg‐phyllosilicates has been observed on Noachian Martian terrains. Therefore, the study of Fe,Mg‐phyllosilicate formation, in order to characterize early Martian environmental conditions, is of particular interest to the Martian community. Previous studies have shown that the investigation of Fe,Mg‐smectite formation alone helps to describe early Mars environmental conditions, but there are still large uncertainties in terms of pH range, oxic/anoxic conditions, etc. Interestingly, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 79 publications
3
16
0
Order By: Relevance
“…A similar observation was inferred by Viennet et al. (), and it may indicate that NIR is more sensitive for discriminating such minerals.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A similar observation was inferred by Viennet et al. (), and it may indicate that NIR is more sensitive for discriminating such minerals.…”
Section: Discussionsupporting
confidence: 88%
“…; Viennet et al. ), but before only reacted at fully saturated conditions. Major element composition of the original basalt is presented in Table .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better characterize the environment of weathering, we use here the mineral associations as a proxy and discuss the conditions of the system drawn from a terrestrial analog study (Gaudin et al, ), geochemical modeling (Zolotov & Mironenko, ), and laboratory experiments (Gaudin et al, ; Viennet et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…If Mars experienced a humid climate for a long time, a dense atmosphere mostly composed of CO 2 and lower amounts (few percent) of other greenhouse gasses is required (Wordsworth et al, 2017). Under such climatic conditions, both geochemical models (Schaefer, 1990;Zolotov & Mironenko, 2016) and laboratory experiments (Gaudin et al, 2018;Viennet et al, 2017) have shown the coprecipitation of hydrated minerals and small amounts of carbonates. Therefore, the apparent absence of carbonates in these weathering profiles remains enigmatic and debates on inhibited formation or subsequent dissolution of the carbonates are yet inconclusive (Edwards & Ehlmann, 2015).…”
Section: Introductionmentioning
confidence: 99%